Analysis of AID for trade on Uganda's trade performance - AKORAEBIRUNGI, John (KDI School, 2016)
The gainful participation of developing countries like Uganda in international trade activities is not affected by foreign market access but mostly domestic supply constraints. Among them include reliable production capacity, poor quality products, and poor infrastructure. WTOkick started the “Aid for Trade” (AFT) undertaking in 2005 with major focus on helping developing countries overcome the fore mentioned challenges. Taking Uganda as the case study, I critically examine the role played by Aid for Trade in strengthening the overall domestic trade capacity. However from the analysis there is little evidence on the impact of this initiative specifically on exports compared to the imports. However it is worth noting that whereas some effort is noticed in trying to enhance Uganda’s capacity to trade, I strongly in this paper recommend that the forth coming aid support to Uganda be channeled into unleashing Uganda’s domestic productive capacity, improving on the economic infrastructure, emphasizing on quality improvement and finally Trade policy formulation should be strengthened if Uganda is to benefit from the AFT initiative.
Thesis(Master) --KDI School:Master of Development Policy,2016